GMAT Question of the Day - Daily to your Mailbox; hard ones only

 It is currently 14 Dec 2018, 23:25

### GMAT Club Daily Prep

#### Thank you for using the timer - this advanced tool can estimate your performance and suggest more practice questions. We have subscribed you to Daily Prep Questions via email.

Customized
for You

we will pick new questions that match your level based on your Timer History

Track

every week, we’ll send you an estimated GMAT score based on your performance

Practice
Pays

we will pick new questions that match your level based on your Timer History

## Events & Promotions

###### Events & Promotions in December
PrevNext
SuMoTuWeThFrSa
2526272829301
2345678
9101112131415
16171819202122
23242526272829
303112345
Open Detailed Calendar
• ### Free GMAT Strategy Webinar

December 15, 2018

December 15, 2018

07:00 AM PST

09:00 AM PST

Aiming to score 760+? Attend this FREE session to learn how to Define your GMAT Strategy, Create your Study Plan and Master the Core Skills to excel on the GMAT.

# D01-41

Author Message
TAGS:

### Hide Tags

Manager
Joined: 21 Sep 2015
Posts: 77
Location: India
GMAT 1: 730 Q48 V42
GMAT 2: 750 Q50 V41

### Show Tags

03 Jul 2016, 02:20
The equation x^2+ax−b=0 has equal roots, and one of the roots of the equation x^2+ax+15=0 is 3. What is the value of b?

Alternate method:

Concept: General form of Quadratic Equation = x^2 +Bx +C

Sum of roots = -B
Product of roots = C

From second equation we get product of roots = 15 and one of the roots is 3
Therefore second root must be 5
Sum = 8
Therefore a = -8

Sum of roots is common to both equations (a)
Roots are equal for first equation

2 * root = -8
Therefore root of equation 1 = -4

Product of roots is 16

Hence equation becomes x^2+ax+16=0

Therefore b = -16
_________________

Appreciate any KUDOS given !

Intern
Joined: 16 Jul 2015
Posts: 40
GMAT 1: 580 Q37 V33
GMAT 2: 580 Q39 V31
GMAT 3: 560 Q40 V28
GMAT 4: 580 Q37 V32
GMAT 5: 680 Q45 V37
GMAT 6: 690 Q47 V37

### Show Tags

10 Jul 2016, 01:53
d=(−8)2+4b=0d=(−8)2+4b=0 . Solving for bb gives b=−16b=−16.
Not clear as to why we are placing value of a in the above equation.
Since equal roots,as per what I understand ,we should be placing the value in this equation.b^2-4ac=0
But I know that there is some other approach to it and I am unclear about that.
Intern
Joined: 16 Jul 2016
Posts: 19

### Show Tags

20 Jul 2016, 18:19
Bunuel Why is the discriminant zero if it has equal roots?
Math Expert
Joined: 02 Sep 2009
Posts: 51215

### Show Tags

21 Jul 2016, 02:01
manik919 wrote:
Bunuel Why is the discriminant zero if it has equal roots?

Check below links for some theory on algebra:

Theory on Algebra: algebra-101576.html
Algebra - Tips and hints: algebra-tips-and-hints-175003.html

DS Algebra Questions to practice: search.php?search_id=tag&tag_id=29
PS Algebra Questions to practice: search.php?search_id=tag&tag_id=50

Special algebra set: new-algebra-set-149349.html

Hope this helps.
_________________
Manager
Joined: 01 Nov 2016
Posts: 66
Concentration: Technology, Operations

### Show Tags

16 Apr 2017, 12:07
Bunuel wrote:

Expression $$b^2-4ac$$ is called discriminant:
• If discriminant is positive quadratics has two roots;
• If discriminant is negative quadratics has no root;
• If discriminant is zero quadratics has one root.

Check more HERE.

Great explanation, thank you
Intern
Joined: 24 Jun 2017
Posts: 35
Location: Singapore
GMAT 1: 660 Q46 V34
GPA: 3.83

### Show Tags

30 Aug 2017, 05:40
Bunuel wrote:
Official Solution:

The equation $$x^2 + ax - b = 0$$ has equal roots, and one of the roots of the equation $$x^2 + ax + 15 = 0$$ is 3. What is the value of b?

A. $$-\frac{1}{64}$$
B. $$-\frac{1}{16}$$
C. $$-15$$
D. $$-16$$
E. $$-64$$

Since one of the roots of the equation $$x^2 + ax + 15 = 0$$ is 3, then substituting we'll get: $$3^2+3a+15=0$$. Solving for $$a$$ gives $$a=-8$$.

Substitute $$a=-8$$ in the first equation: $$x^2-8x-b=0$$.

Now, we know that it has equal roots thus its discriminant must equal to zero: $$d=(-8)^2+4b=0$$. Solving for $$b$$ gives $$b=-16$$.

Why you substitute the -8 back into the first equation? what is the relation between the two equations?
I know my question might be stupid but I am not getting what they are asking, maybe it´s my english...
thanks!!
Intern
Joined: 25 Dec 2017
Posts: 4

### Show Tags

16 Jan 2018, 10:11
I don't really know where I am going wrong.

$$x^2+ax−b=0$$ has equal roots, and one of the roots of the equation $$x^2+ax+15=0$$ is 3

$$3^2 + 3a + 15 = 0$$

$$3a = -15 - 9$$

$$3a = -24$$

$$a = -8$$ Substituting it in 1st equation

$$x^2-8x-b=0$$ because we know it has equal roots, we can put x = 3 in equation 1
$$9-8(3)-b=0$$
$$-b = -9+24$$
$$b = -15$$

Isn't this correct?
Math Expert
Joined: 02 Sep 2009
Posts: 51215

### Show Tags

16 Jan 2018, 20:23
1
vinod94 wrote:
I don't really know where I am going wrong.

$$x^2+ax−b=0$$ has equal roots, and one of the roots of the equation $$x^2+ax+15=0$$ is 3

$$3^2 + 3a + 15 = 0$$

$$3a = -15 - 9$$

$$3a = -24$$

$$a = -8$$ Substituting it in 1st equation

$$x^2-8x-b=0$$ because we know it has equal roots, we can put x = 3 in equation 1
$$9-8(3)-b=0$$
$$-b = -9+24$$
$$b = -15$$

Isn't this correct?

$$x^2 + ax - b = 0$$ has equal roots, means that its discriminant is zero. For example, (x - 3)^2 = 0, (2x + 1)^2 = 0, ... so basically any (ax - b)^2 = 0 has has equal roots: two same roots.

$$x^2 + ax - b = 0$$ has equal roots does not mean that it has equal root with $$x^2 + ax + 15 = 0$$, so x = 3 might not be the root of $$x^2 + ax - b = 0$$.
_________________
Intern
Joined: 02 Jun 2015
Posts: 22
Location: United States

### Show Tags

06 Jun 2018, 14:30
Since the roots in the 1st equation are equal, b has to be a perfect square.

So eliminate A, B and C.

Between D and E, try to plug in b= -16 then it will be (x - 4) (x - 4) = x^2 - 8x +16

That's a match! Answer choice D

Thanks!
Alecita
Intern
Joined: 02 Jun 2015
Posts: 22
Location: United States

### Show Tags

10 Jun 2018, 09:23
This is a tricky one. Since the 1st equation has equal roots, "b" has to be a perfect square.
Eliminate A, B and C.

Between D and E, plug in b=-16 then we'll have (x-4)^2 that will match x^2 - 8x + 16 = 0.

Thanks!
Alecita
Intern
Joined: 14 Jun 2018
Posts: 1

### Show Tags

17 Jun 2018, 06:44
I don't agree with the explanation. by subsituting a= -8 and x = 3, b= -15
Intern
Joined: 02 Jun 2015
Posts: 22
Location: United States

### Show Tags

11 Jul 2018, 15:31
Since the 1st equation has equal roots, b has to be a perfect square. This way, eliminate answer choices A, B and C.

In the 2nd equation one of the roots is 3, so plug in x=3 then we'll get a=-8

Between answer choices D and E, choose -16 that will give (x-4) (x-4) = x^2 - 8x + 16 which match a=-8

Thanks!
Alecita
Manager
Joined: 10 May 2018
Posts: 125
Concentration: Finance, Sustainability

### Show Tags

23 Jul 2018, 01:08
Allow me to clarify. You are confusing two different statements mentioned in the question about two different quadratic equations. Here check this complete and clear solution by Bunuel.
iPriya07 wrote:
I don't agree with the explanation. by subsituting a= -8 and x = 3, b= -15

_________________

Stuck in the 600-700 score bracket? I welcome you to read my four-step course of action to a modest score.
I also invite you to critique and help me find flaws in my modus operandi. Thanks!

Study Buddy Forum Moderator
Joined: 04 Sep 2016
Posts: 1267
Location: India
WE: Engineering (Other)

### Show Tags

29 Jul 2018, 01:21
1
Bunuel chetan2u niks18 gmatbusters KarishmaB

Quote:
The equation $$x^2 + ax - b = 0$$ has equal roots, and one of the roots of the equation $$x^2 + ax + 15 = 0$$ is 3. What is the value of b?

Could this also be solved using

$$x^2$$ - (Sum of roots)*x + (Product of roots)= 0

To validate my understanding, x is variable in question stem, where as a and b are constants.
_________________

It's the journey that brings us happiness not the destination.

Math Expert
Joined: 02 Aug 2009
Posts: 7106

### Show Tags

29 Jul 2018, 03:15
2
Bunuel chetan2u niks18 gmatbusters KarishmaB

Quote:
The equation $$x^2 + ax - b = 0$$ has equal roots, and one of the roots of the equation $$x^2 + ax + 15 = 0$$ is 3. What is the value of b?

Could this also be solved using

$$x^2$$ - (Sum of roots)*x + (Product of roots)= 0

To validate my understanding, x is variable in question stem, where as a and b are constants.

So let the roots in second case be 3and z, so $$3z=15...z=5$$
So sum of roots =3+5=8, a=-8
The first equation becomes $$x^2-8x-b=0$$..
it can be written in $$x^2-2xy+y^2=0$$ to get $$(x-y)^2$$ and thus equal roots..
So $$x^2-2*4*x+4^2=0$$ so $$b=-4^2$$
_________________

1) Absolute modulus : http://gmatclub.com/forum/absolute-modulus-a-better-understanding-210849.html#p1622372
2)Combination of similar and dissimilar things : http://gmatclub.com/forum/topic215915.html
3) effects of arithmetic operations : https://gmatclub.com/forum/effects-of-arithmetic-operations-on-fractions-269413.html

GMAT online Tutor

Veritas Prep GMAT Instructor
Joined: 16 Oct 2010
Posts: 8678
Location: Pune, India

### Show Tags

30 Jul 2018, 03:32
1
Bunuel chetan2u niks18 gmatbusters KarishmaB

Quote:
The equation $$x^2 + ax - b = 0$$ has equal roots, and one of the roots of the equation $$x^2 + ax + 15 = 0$$ is 3. What is the value of b?

Could this also be solved using

$$x^2$$ - (Sum of roots)*x + (Product of roots)= 0

To validate my understanding, x is variable in question stem, where as a and b are constants.

Yes, as shown by chetan2u above and in fact you can continue to use the same approach in the last steps also:

$$x^2 + ax + 15 = 0$$
If one root is 3, the other is 5 (to get the product 15). So sum of the roots is 8.
This means a = -8

The other equation becomes $$x^2 - 8x - b = 0$$
The sum of the roots is 8 and the roots are equal to they will be 4 and 4. Their product becomes 16. So b becomes -16.
_________________

Karishma
Veritas Prep GMAT Instructor

Intern
Joined: 16 Jan 2018
Posts: 14

### Show Tags

14 Aug 2018, 07:23
Bunuel wrote:
Official Solution:

The equation $$x^2 + ax - b = 0$$ has equal roots, and one of the roots of the equation $$x^2 + ax + 15 = 0$$ is 3. What is the value of b?

A. $$-\frac{1}{64}$$
B. $$-\frac{1}{16}$$
C. $$-15$$
D. $$-16$$
E. $$-64$$

Since one of the roots of the equation $$x^2 + ax + 15 = 0$$ is 3, then substituting we'll get: $$3^2+3a+15=0$$. Solving for $$a$$ gives $$a=-8$$.

Substitute $$a=-8$$ in the first equation: $$x^2-8x-b=0$$.

Now, we know that it has equal roots thus its discriminant must equal to zero: $$d=(-8)^2+4b=0$$. Solving for $$b$$ gives $$b=-16$$.

Dear Bunuel

The way the question is typed, shouldn't b be equal to +16 (and not -16)? Because the equation has already a - sign before b, if we plug in the answer -16, the equation becomes x^2-8x-(-16)=0, which is x^2-8x+16=0 and does not have equal roots

Intern
Joined: 17 Jul 2018
Posts: 19

### Show Tags

15 Aug 2018, 18:20
I don't think it's fair to say knowing the discriminant rules are "the fundamentals".

Most test takers will have to guess and check after figuring out that a= -8
Manager
Joined: 21 Jul 2018
Posts: 50

### Show Tags

25 Sep 2018, 10:07
Bunuel wrote:
Official Solution:

The equation $$x^2 + ax - b = 0$$ has equal roots, and one of the roots of the equation $$x^2 + ax + 15 = 0$$ is 3. What is the value of b?

A. $$-\frac{1}{64}$$
B. $$-\frac{1}{16}$$
C. $$-15$$
D. $$-16$$
E. $$-64$$

Since one of the roots of the equation $$x^2 + ax + 15 = 0$$ is 3, then substituting we'll get: $$3^2+3a+15=0$$. Solving for $$a$$ gives $$a=-8$$.

Substitute $$a=-8$$ in the first equation: $$x^2-8x-b=0$$.

Now, we know that it has equal roots thus its discriminant must equal to zero: $$d=(-8)^2+4b=0$$. Solving for $$b$$ gives $$b=-16$$.

ephes Feel mistake in highlighted part
_________________

______________________________
Consider KUDOS if my post helped !!

I'd appreciate learning about the grammatical errors in my posts

Please let me know if I'm wrong somewhere

Intern
Joined: 06 Apr 2018
Posts: 19

### Show Tags

06 Oct 2018, 08:38
I solved it to the point, a=-8.

Then, used the approach sum of roots = -b/a (if the equation is of the form ax2 +bx+c)

So the sum is 8/1= 8 =2x (since the roots are same). This is how I got the value of x=4

Then after that using the method of substitution I could get the value of b.

x(square)+ ax-b=0
(4*4)+4(-8)-b=0
16-32-b=0
-16-b=0
Hence b=-16

Please let me know if my approach is correct.
Re: D01-41 &nbs [#permalink] 06 Oct 2018, 08:38

Go to page   Previous    1   2   3    Next  [ 42 posts ]

Display posts from previous: Sort by

# D01-41

Moderators: chetan2u, Bunuel

 Powered by phpBB © phpBB Group | Emoji artwork provided by EmojiOne Kindly note that the GMAT® test is a registered trademark of the Graduate Management Admission Council®, and this site has neither been reviewed nor endorsed by GMAC®.